Circumplex model of affect of valence domain among young adults : an ERP study - Sukarno, Nadiah Mohd (2021)
Introduction: This study is looking at the valence domain in the Circumplex Model of Affect. Valence domain in the model ranging from negative to positive emotion. Visual stimuli taken from the International Affective Picture System (IAPS) were used to evoke negative, neutral, and positive emotion (valence effect). IAPS is a standardised stimulus range that is regarded as the gold standard for affect ERP research and each pictures have its own normative value. Objective: The aim of this research is to examine the correspondence of EEG-ERP valence data (P300, N200) with the normative valence from IAPS. This research also wants to identify the source of localization of P300 and N200 with regards to the different levels (high, moderate, low) of emotional valence processing Methodology: 35 young adults aged 19-24 years old passively viewed 15 valence IAPS images and their brain’s responses to the images were recorded using EEG Cap. Friedman Test was performed on the midline electrodes; Fz, Cz, Pz, and Oz for all components; N200 amplitude, N200 latency, P300 amplitude, and P300 latency. Results: Statistic shows that valence effect (brain responses to the valence stimulus) is on ERP component P300 latency at Fz but the findings does not correspond with IAPS data. Different sources of localization were identified at Brodmann Areas 11, 17, and 38, with the frontal, temporal, and occipital lobes in different levels of emotional valence but similar in both ERP components; N200 and P300. Conclusion: Findings does not correspond to IAPS findings because the valence effect in this study is found in neutral & positive images where IAPS’ finding is on negative images. Neutral and positive images evoke more valence effect in participant and it contradicts with IAPS. This shows that emotion and response to it is affected by factors such as culture and individual differences.